2022
DOI: 10.1371/journal.pgph.0000177
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to COVID-19 preventive measures and its association with intimate partner violence among women in informal settings of Kampala, Uganda

Abstract: Cases of coronavirus disease 2019 (COVID-19) detected, and COVID-19 associated mortality increased since the first case was confirmed in Uganda. While adherence to WHO-recommended measures to disrupt COVID-19 transmission has since been implemented, it has been reported to be sub-optimal. An increase in intimate partner violence (IPV) cases was linked to enforcement of COVID-19 lockdowns and other preventive measures especially in informal settings of Kampala. We determined the association between adherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The prevalence of COVID-19 of 8.0% reported by this study was within the national level situational reports ndings (12)(13)(14). The studied community neighbors the parks where gorilla tourism is the key economic activity.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of COVID-19 of 8.0% reported by this study was within the national level situational reports ndings (12)(13)(14). The studied community neighbors the parks where gorilla tourism is the key economic activity.…”
Section: Discussionsupporting
confidence: 79%
“…The COVID-19 lockdown closed this traditional avenue for help-seeking in countries like Zimbabwe. A growing number of prevalence studies identified increases in violence against women and children (for example, in Uganda and South Africa [17,18]), but only one other study to our knowledge examined violence help-seeking. Decker et al [19] prospectively found that women and girls in Nairobi, Kenya increased help-seeking for intimate partner violence and sexual violence during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the level of adjustments in the way of living was also intense in a very short time. Consequences of this rapid change in how people live have been reported, including worsening of mental health problems and gender-based violence [ 90 ]. The challenge is even greater for refugees, especially the newly arrived, who may still have problems adjusting to the new environment and the new social and cultural realities, which have further implications for their wellbeing [ 91 ].…”
Section: Discussionmentioning
confidence: 99%